Identification and Expression Analysis of CAMTA Genes in Tea Plant Reveal Their Complex Regulatory Role in Stress Responses - Zhou, Qiying; Zhao, Mingwei; Xing, Feng; Mao, Guangzhi; Wang, Yijia; Dai, Yafeng; Niu, Minghui; Yuan, Hongyu (Frontiers in Plant Science, 2022)
Calmodulin-binding transcription activators (CAMTAs) are evolutionarily conserved transcription factors, and have multi-functions in plant development and stress response. However, identification and functional analysis of tea plant (Camellia sinensis) CAMTA genes (CsCAMTAs) is still lacking. Here, five CsCAMTAs were identified from tea plant genomic database. Their gene structures were similar except CsCAMTA2, and protein domains were conserved. Phylogenetic relationship classified the CsCAMTAs into three groups, CsCAMTA2 was in group I, CsCAMTA1, 3 and CsCAMTA4, 5 were respectively in group II and III. Analysis showed that stress and phytohormone response related cis-elements were distributed in the promoters of CsCAMTA genes. Expression analysis showed that CsCAMTAs were differentially expressed in different organs and under various stress treatments of tea plants. 300 and 401 positive co-expressed genes of CsCAMTAs were identified under cold and drought, respectively. CsCAMTAs and their co-expressed genes constituted five independent co-expression networks. KEGG enrichment analysis of CsCAMTAs and the co-expressed genes revealed that hormone regulation, transcriptional regulation, and protein processing related pathways were enriched under cold treatment, while pathways like hormone metabolism, lipid metabolism, carbon metabolism were enriched under drought treatment. Protein interaction network analysis suggested that CsCAMTAs could bind (G/A/C)CGCG(C/G/T) or (A/C)CGTGT cis element in the target gene promoters, and transcriptional regulation might be the main way of CsCAMTA mediated functional regulation. The study establishes a foundation for further function studies of CsCAMTA genes in stress response.